Diagenesis and fluid evolution in the third member of the Eocene Shahejie Formation, Bonan Sag, Bohai Bay Basin, China. (June 2021) - Han, Shujun; Yu, Bingsong; Ruan, Zhuang; Bai, Chenyang; Shen, Zhenhuan; Löhr, Stefan C.
Abstract: Diagenesis significantly influences sandstone reservoir quality, so that a detailed understanding of diagenesis is essential for the identification and prediction of favorable reservoirs. Several studies have been conducted on individual sandstone reservoirs in the Bonan Sag, a typical half-graben, oil-producing sag in eastern China, but few have explicitly considered the potential impact of the asymmetric shape of the sag, which is steep in the north and gentle in the south. This research takes full consideration of the tectonic setting and distribution of source rocks in the sag to compare the style, magnitude and timing of diagenesis in the northern Steep Slope and Sag Zone (SSSZ) and the southern Gentle Slope Zone (GSZ) by means of drill core observations, thin section petrography, high resolution scanning electron microscopy, fluid inclusion microthermometry, as well as cathodoluminescence and carbonate stable isotope analysis. Petrographic observations identify the wide-spread occurrence of authigenic quartz and clay minerals in association with dissolved feldspar, as well as abundant carbonate cements occurring as several distinct generations due to evolving pore fluid composition. The SSSZ has variable carbonate mineralogy while ankerite dominates in the GSZ. The homogenization temperature of fluid inclusions in authigenic quartz in the SSSZ has a wider range (93°C–157.9 °C) and lower starting temperature (93 °C) compared with the GSZ (106.2 °C) and is characterized by more lighter carbonate δ 13 C and δ 18 O values (δ 18 O: −14.8‰ -11.3‰, δ 13 C: 1.1‰–2.7‰ for the SSSZ; δ 18 O: −11.9‰ -5.8‰, δ 13 C: 2.9‰–5.5‰ for the GSZ). The results indicate that (1) Diagenetic conditions in the Bonan Sag evolved from alkaline to acidic to alkaline in general, but with distinct late stage carbonate cementation in SSSZ vs GSZ; (2) the diagenetic processes as well as the nature of pore waters varied across different zones and also temporally. Acidic conditions in the SSSZ started earlier and persisted for longer than in the GSZ. (3) The regional differentiation of the diagenetic processes and pore fluid evolution result from the source rock distribution and burial histories which differ across the Bonan Sag because of the asymmetric shape of the half-graben. We propose a model of fluid evolution over space and time which may provide a new framework for understanding the diagenetic processes and the fluid evolution of oil-producing sags and also contribute to the prediction of favorable reservoirs. Highlights: The E s 3 in Bonan Sag went through an alkaline-acid-alkaline diagenetic conditions. The structure of the sag leads to temporal and spatial differences in diagenesis. Source rock distribution and burial histories are significant controls in diagenesis. A temporal and spatial diagenesis evolution model was put forward.